Oligodendrocyte Bioenergetics in Health and Disease. (August 2019) - Rosko, Lauren; Smith, Victoria N.; Yamazaki, Reiji; Huang, Jeffrey K.
The human brain weighs approximately 2% of the body; however, it consumes about 20% of a person's total energy intake. Cellular bioenergetics in the central nervous system involves a delicate balance between biochemical processes engaged in energy conversion and those responsible for respiration. Neurons have high energy demands, which rely on metabolic coupling with glia, such as with oligodendrocytes and astrocytes. It has been well established that astrocytes recycle and transport glutamine to neurons to make the essential neurotransmitters, glutamate and GABA, as well as shuttle lactate to support energy synthesis in neurons. However, the metabolic role of oligodendrocytes in the central nervous system is less clear. In this review, we discuss the energetic demands of oligodendrocytes in their survival and maturation, the impact of altered oligodendrocyte energetics on disease pathology, and the role of energetic metabolites, taurine, creatine, N -acetylaspartate, and biotin, in regulating oligodendrocyte function.